Gigantes do telejornalismo mundial Mutações editoriais e tecnológicas das agências internacionais de notícias - Esperidião, Maria Cleidejane Silva (2011)
This thesis focuses on the history of the news agencies‟ audiovisual divisions that act on an international scale (Reuters Television and Associated Press Television News), delimitating their operational characteristics within the informational flow, particularly the television news channels. It demonstrates, through the examination of case studies by Reuters TV and APTN, how the global news ecosystem functions, geared towards the broadcasting stations. This thesis carefully examines how this ecosystem behaves faced with the impact of the development of new media deriving from the web. It shows how the development of network digital technology led to editorial and logistical changes in the productive routine within the agencies, seen in this study as globalization‟s important social actors. Upon charting the agencies‟ commercial and structural dynamics, the hypothesis upheld here is that the vast majority of the news transmitted by these companies is determined by the political and economic interests of their biggest clients, which leads us to ratify, even today, 30 years after UNESCO‟s McBride Report was published, that there is still a great asymmetry in the international news in which countries, regions and subject matters are neglected and excluded. By looking upon the content of both agencies‟ output, the author concludes that western-led news agencies now appear to report an expressive number of stories dedicated to Asia. This thesis also claims that the bulk of their content is fed with news related to The United States and Western Europe. It shows that during dramatic and catastrophic media events, Reuters TV and APTN reassure their symbolic role by selling the idea of their news: unbiased, with accountability, diversity of themes and social actors. In these same events, news agencies also reinforce their role by organizing and packing the news. They also feed the global news system with constancy, speed and security.